If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-2)=3x+1
We move all terms to the left:
(x-2)-(3x+1)=0
We get rid of parentheses
x-3x-2-1=0
We add all the numbers together, and all the variables
-2x-3=0
We move all terms containing x to the left, all other terms to the right
-2x=3
x=3/-2
x=-1+1/2
| -4+2b=7b-3 | | x-8=2(2x-22) | | 3300+75x=1 | | 1/5y=y=5 | | 10x-29/7=4x-35 | | {y}{8}=58y =5 | | 2x-4+3x+14=35 | | 6x+2=3(2x−1) | | 7x-5=10×-x-15 | | 2x3-5=59 | | 2(6x+1)=14x-6 | | 0.375*x=-0.46875 | | 10w+-12w=-14 | | 0.3s+0.3=1.5 | | x=-32+6/25 | | -2+5(5-6x)=83 | | 12=18w-36=0 | | 21=-4x+8 | | 14x-1+9=9x-22 | | 6x+2=3(2x−1 | | 6(3x+6)+7(x+5)=46 | | b+9=17b= | | 3225+100x=1 | | 6c+8=-2+8c | | -8w=-10w-32 | | (2x+1)+(10x-10)+(3x+14)=180 | | 47x=34 | | 4(w+18)=4 | | 14=-3m-7 | | 3(4+7n)=-7+2n | | 3(x-4)=x-4+6x | | 4x+6=(3x+2) |